P1378PROCESS NORMALIZATION AND CLINICAL OUTCOMES FOLLOWING IMPLEMENTATION OF THE ANEMIA CONTROL MODEL FOR PERSONALIZED ANEMIA MANAGEMENT. (6th June 2020) - Neri, Luca; Cattinelli, Isabella; Bolzoni, Elena; Barbieri, Carlo; Ramos Sanchez, Rosa; Stuard, Stefano
Abstract: Background and Aims: Anemia management is still challenging in a large share of dialysis patients. ESA resistance show wide variations across patients as well as fluctuations along time within the same patient. The Anemia Control Model (ACM) is a software application which can be integrated in electronic health record systems. ACM is based on an artificial neural network system trained on 1 million health records which simulates patient's personalized dose-response relationship to ESA and Iron. Based on patients' response forecast, ACM suggests the optimal drug dose recommendations to reach or maintain the hemoglobin level within target and to minimize the drug consumption. The ACM has earned medical device certification and it is currently used in 13 countries within the EMEA FMC network. Effectiveness and safety of ACM has been demonstrated in previous real-world evidence studies. We report ACM use and its clinical outcomes among hemodialysis patients registered in the Spanish FME Network Method: We recorded all medical prescriptions and their clinical outcome for which an ACM recommendation was computed (ACM prescription). prescription occurred in 9 clinics located in Catalunya (Spain) from September 2017 to September 2018. We report dynamics of ACM suggestion acceptance rate, ESA consumption and Hb target achievement in the study period. Results: There were 1189 active patients per month during the study period on average. ACM suggestion acceptance rate was 73, 3%. ESA monthly consumption ranged from 234:7±281:9 – 310.2 ± 310:8 UI/Kg; 86% of patients receiving ESA doses according to ACM recommendations achieved or remained within Hb target range; on the contrary, when physicians rejected ACM recommendations and prescribed a different dosage, only 77% of patients reached or maintained the Hb level on target (p<0.05). Conclusion: Our study demonstrated that ACM suggestions were frequently accepted by physicians. Acceptance of ACM suggestion was associated with higher Hb target achievement.